1996
DOI: 10.1192/s0007125000298310
|View full text |Cite
|
Sign up to set email alerts
|

ICI 204, 636: A New Atypical Antipsychotic Drug

Abstract: The therapeutic effects of ‘classic’ (typical) antipsychotic agents lie in their ability to block central dopaminergic receptors – a property that is also responsible for the frequent occurrence of undesirable extrapyramidal side-effects (EPS). In contrast to these typical agents, clozapine alone has distinguished itself in humans – by virtue of its enhanced antipsychotic action and lack of concurrent EPS – as an atypical antipsychotic. However, the use of clozapine has been limited by the occurrence of agranu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 17 publications
(23 reference statements)
1
21
0
1
Order By: Relevance
“…Because several controlled clinical studies have con-84 J. Arnt and T. Skarsfeldt firmed antipsychotic activity of both sertindole (e.g., Zimbroff et al 1997) and quetiapine (e.g., Hirsch et al 1996), it is obvious that AMPH discrimination is not an animal model of schizophrenia. Instead it has been suggested that the AMPH inhibition is a measure of inhibitory effects on the DA reward system and accordingly that the model may be relevant for evaluation of the so-called neuroleptic-induced deficit syndrome (for further discussion and references, see Amt 1996; Brauer et al 1997).…”
Section: Operant Responding Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because several controlled clinical studies have con-84 J. Arnt and T. Skarsfeldt firmed antipsychotic activity of both sertindole (e.g., Zimbroff et al 1997) and quetiapine (e.g., Hirsch et al 1996), it is obvious that AMPH discrimination is not an animal model of schizophrenia. Instead it has been suggested that the AMPH inhibition is a measure of inhibitory effects on the DA reward system and accordingly that the model may be relevant for evaluation of the so-called neuroleptic-induced deficit syndrome (for further discussion and references, see Amt 1996; Brauer et al 1997).…”
Section: Operant Responding Patternsmentioning
confidence: 99%
“…One caveat to this conclusion must be mentioned. In our hands, quetiapine possesses a classic profile in the VTA/SNC model, but the available clinical data (Casey 1996a;Hirsch et al 1996) indicate that quetiapine induces less EPS in schizophrenic patients than does haloperidol. The reason for the discrepancy is at present unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main importance of this is that D 2 receptor antagonism may be related to PRL increase and consequently sexual dysfunction. 3 The frequent sexual side effects associated with conventional antipsychotics tend to be dose-related, and the primary underlying mechanism is likely to be the direct dopamine antagonist effect of this type of agent, with some additional indirect effects due to elevated PRL levels. 4 There are only few reports regarding both typical and atypical antipsychoticassociated SDs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared with conven tional antipsychotic drugs, quetiapine is associated with fewer instances of extrapyramidal side effects, agranulocytosis, and hyperprolactinemia. [3][4][5][6][7] Quetiapine is marketed in tablet and fine particle formula tions; fumarate salt ( Fig. 1(I)) is the principal agent.…”
mentioning
confidence: 99%